Phylogeography of the pelagic snail Limacina helicina (Gastropoda: Thecosomata) in the subarctic western North Pacific. (10th November 2017) - Shimizu, Keisuke; Kimoto, Katsunori; Noshita, Koji; Wakita, Masahide; Fujiki, Tetsuichi; Sasaki, Takenori
Abstract: The genetic diversity of one of the most abundant species in the Arctic and subarctic oceans, the pelagic snail Limacina helicina, has not yet been characterized in the north Pacific. This species has different 'forma' ( L. helicina forma helicina, acuta, pacifica and ochotensis ), but whether or not the morphological differences between these forma are caused by phenotypic plasticity or genetic differentiation remains unclear. Here, we analysed partial nucleotide sequences of the mitochondrial cytochrome c oxidase subunit I gene in L. helicina from the subarctic western North Pacific Ocean (SWNP; L. helicina f. acuta ) and compared them with those from Svalbard ( L. helicina f. helicina ) and other localities (Beaufort Sea, eastern Pacific, northern Sea of Japan and western Atlantic). The results show clear genetic differentiation between populations in the SWNP and Svalbard (Φ CT = 0.59282, P < 0.001). These genetic differences are consistent with the previous description of the two forma L. h. f. acuta (SWNP) and L. h. f. helicina (Svalbard) based on shell morphology.